ANALISIS DAYA SAING INDUSTRI PARIWISATA KABUPATEN CILACAP - Hartsa Kusuma Nagara; Farah Wulandari Pangestuty (Journal of Development Economic and Social Studies, 2022)
The tourism industry can move the wheels of the regional economy on a small or medium scale up. This is what encourages local governments to compete to optimize their tourism potential. Cilacap Regency is one of the regencies that has a tourism industry which is currently not the leading sector in its regional revenue but from a period of time that continues to progress. The purpose of this study is to determine the development of the competitiveness of the tourism sector in Cilacap regency by using a competitiveness monitor analysis. The results show that the tourism competitiveness of Cilacap Regency on the Environment Indicator (EI), Human Resource Indicator (HRI), Infrastructure Development Indicator (IDI), Social Development Indicator (SDI), Technology Advancement Indicator (TAI) is good but for Human Tourism Indicator (HTI), Price Competitiveness Indicator (PCI) and Openness Indicator (OI) still have a low tourism competitiveness index